2010
DOI: 10.1074/jbc.m109.083626
|View full text |Cite
|
Sign up to set email alerts
|

NF449 Is a Novel Inhibitor of Fibroblast Growth Factor Receptor 3 (FGFR3) Signaling Active in Chondrocytes and Multiple Myeloma Cells

Abstract: The FGFR3 receptor tyrosine kinase represents an attractive target for therapy due to its role in several human disorders, including skeletal dysplasias, multiple myeloma, and cervical and bladder carcinomas. By using molecular library screening, we identified a compound named NF449 with inhibitory activity toward FGFR3 signaling. In cultured chondrocytes and murine limb organ culture, NF449 rescued FGFR3-mediated extracellular matrix loss and growth inhibition, which represent two major cellular phenotypes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 43 publications
0
36
0
1
Order By: Relevance
“…More recently, a selective P2X 1 receptor antagonist NF449 has been shown to block FGFR3 signaling in MM cells. Importantly, NF449 inhibits the kinase activity of disease-associated FGFR3 mutant (K650E) in a fashion that is non-competitive with ATP [17]. Most recent studies show that a novel SM JAK inhibitor, AZD1480, blocks proliferation and survival, associated with inhibition of FGFR3 and JAK/STAT3 signaling in MM cells, cultured alone or with BMSCs [18].…”
Section: Fibroblast Growth Factormentioning
confidence: 96%
“…More recently, a selective P2X 1 receptor antagonist NF449 has been shown to block FGFR3 signaling in MM cells. Importantly, NF449 inhibits the kinase activity of disease-associated FGFR3 mutant (K650E) in a fashion that is non-competitive with ATP [17]. Most recent studies show that a novel SM JAK inhibitor, AZD1480, blocks proliferation and survival, associated with inhibition of FGFR3 and JAK/STAT3 signaling in MM cells, cultured alone or with BMSCs [18].…”
Section: Fibroblast Growth Factormentioning
confidence: 96%
“…This mutation has been exploited in many studies to examine signaling pathways utilized by FGFR3 (14,(39)(40)(41)(42)(43). However, the K650E mutation has not yet been identified together with the FGFR3-TACC3 oncogenic gene fusion in human cancer, and thus represents an artificial construct not yet found in nature.…”
Section: Discussionmentioning
confidence: 99%
“…The BrdU incorporation activity was almost completely abolished by heat or Pronase treatment ( Figure 2B), indicating that the OPC proliferation factor in adult mouse serum must be a heat-sensitive protein. A pharmacological screen revealed that 2 FGF receptor (FGFR) inhibitors, PD173074 and NF449 (30,31), blocked serum-promoted OPC proliferation ( Figure 2, C and D, Supplemental Figure 2C, and Supplemental Table 1), suggesting that the OPC proliferation factor in adult mouse serum belongs to the FGF family. We then sought to determine which FGFRs are involved in serum-promoted OPC proliferation.…”
Section: Ki67mentioning
confidence: 99%